Volatile constituents as complementary tools to characterize seven sardinian Genista species. (October 2015) - Bertoli, Alessandra; Loi, Maria Cecilia; Noccioli, Cecilia; Maxia, Lucia; Moonen, Anna-Camilla; Pistelli, Luisa
Abstract: The aroma fingerprints of seven endemic Sardinian populations of Genista species ( Genista bocchierii, Genista arbusensis, Genista cadasonensis, Genista corsica, Genista morisii, Genista pichisermolliana, Genista sulcitana ) were defined for the first time in order to investigate the relationship between their chemotaxonomic classification and discriminating volatiles. It is the first time that the inter-species compositional variations of non-terpenoidic constituents and target volatiles such as linalool, limonene, 2, 6-nonadienal, 2-pentylfuran, ( E )-2-(2-pentenyl)-furan, ß -caryophyllene and caryophyllene oxide were related by Principal Components Analysis to the actual chemotaxonomic classification of the selected Sardinian Genista species. Although they are not considered marketable aromatic plants, these original results have shown the potential role of volatiles not only as new further important chemotaxonomic markers of Genista species, but also as potential ecological factors in the chemodiversity of some endemic Mediterranean Genista or, more in general, in vegetation changes and reforestation processes. Graphical abstract: Highlights: EO fingerprints were studied as potential chemotaxonomic tools in the genus Genista . Seven Genista species were used as pilot species for Sardinian flora. PCA analysis was performed on volatile chemical classes and singular components. Non-terpenoidic volatiles (aldehydes, furans, alcohols) could play a role as markers.